Megacities, migration and an evolutionary approach to bipolar disorder: a study of Sardinian immigrants in Latin America - Carta, Mauro G. (Braz J Psychiatry, 2019)
OBJECTIVE: To determine whether people with a Sardinian genetic background who live in the megacities of South America have a higher frequency of hypomania than residents of Sardinia. METHODS: A community survey of Sardinian immigrants was carried out in four Brazilian metropoles (n=218) and Buenos Aires (n=306). The results were compared with those of a study involving a similar methodology (Mood Disorder Questionnaire [MDQ] as a screening tool) conducted in seven Italian regions, including a sub-sample from Sardinia. RESULTS: There was a higher prevalence of lifetime hypomania among Sardinians living in the Brazilian metropoles than among those living in Sardinia. This result was also consistent with Sardinian immigrants in Buenos Aires. After stratification by sex and age, the lifetime prevalence of MDQ scores ≥ 8 among Sardinians in South-American megacities and Sardinia was 8.6% vs. 2.9%, respectively (p < 0.0001). CONCLUSIONS: The higher frequency of hypomania in migrant populations appears to favor an evolutionary view in which mood disorders may be a maladaptive aspect of a genetic background with adaptive characteristics.